The Role of Biomulch Arachis pintoi In Increasing Soil Infiltration Rate on Sloping Land of Oil Palm Plantation - Sarjono, Arif; Guntoro, Dwi; Supijatno, Supijatno (Journal of Tropical Crop Science, 2018)
The slope of land in oil palm plantation areas is the one of the primary causes of low soil water content due to low rates of soil infiltration. Biomulch is one of the conservation methods that can be used to cover and shield the soil from weeds, prevent soil erosion, and increase the rate of soil infiltration. Arachis pintoi is a perennial, stoloniferous legume crop that has potentials to be used as biomulch. The objective of the research was to study the role of Arachis pintoi in increasing the rate of soil infiltration on a sloping land of oil palm plantation. The research was conducted on the slope land (22.8%) of the Bukit Kemuning Farmer Group, Mersam, Batanghari, Jambi, Indonesia (01036'21", 102057'11") from September 2017 to March 2018. The environmental design used in this study was a one-factor randomized block design (RBD) with five ground cover treatments, i.e. natural vegetation, Arachis pintoi, Centrosema pubescens, Pueraria javanica and Calopogonium mucunoides. The results showed that the average growth rate of A. pintoi was 2.47 cm per week, which was lower than the growth of other treatments. The root length of A. pintoi was 50.36 cm at 20 weeks after planting. A. pintoi can be used as biomulch; sloping land planted with A. pintoi had an infiltration rate of  49.30 cm per hour at 20 week after planting, i.e. an increase of 32.47% compared to the infiltration rate with the natural vegetation.Keywords: land cover crop, Centrosema pubescens, Pueraria javanica, Calopogonium mucunoides